The analysis of the defects causes on the surface of the rolling train wheels - Vakulenko, I. O.; Perkov, O. M.; Anofriev, V. H.; Krot, V. S. (Science and Transport Progress, 2008)
The destruction occurrence in a railroad wheel is caused by formation of the high local stresses produced by the inhomogeneous elastic-plastic deformation when the cyclic temperature change takes place during and after braking using brake shoes.